Methods for epidemiological study of injuries to professional football players: developing the UEFA model - Hägglund, M; Walden, M.; Bahr, R.; Ekstrand, J. (British Journal of Sports Medicine, 2005)
A problem with epidemiological studies of football injuries is the inconsistent manner in which injury is defined and data are collected. Projects have been initiated to study the incidence and causes of injury in football, but there is no uniformly accepted reporting system. In this report, some common pitfalls encountered in the recording of injury are addressed, and practical guidelines for epidemiological studies are provided. An injury reporting system developed for the UEFA Football Safety Project for studies on professional footballers is used as a starting point for a general discussion on injury registration and compared with other existing reporting systems. The recording definition of injury may vary between studies depending on its purpose. A time loss injury definition is practical for all playing levels, and, as a minimum, results on time loss injuries should therefore always be reported separately to allow direct comparisons between studies. There is a need to agree on a uniform sports injury classification system with corresponding diagnostic criteria, as well as standardised return to play criteria after injury.